Exhibitions on Women in Science: Public Understanding of Science and Gender Social Inclusion - Dahmouche, Mônica Santos; Pinto, Simone Pinheiro; Silva, Camila Silveira da; Jordão, Thais (Cadernos de Educação Tecnologia e Sociedade, 2022)
The issue of women's representativeness in science has been addressed in the literature from different perspectives. The present article intends to explore the path of organizing three exhibitions that shed light on some women from the national scientific scene, held in different geographical contexts, as strategies for discussing gender relations in Brazilian science, in actions of public understanding of science and social inclusion. The study addresses some issues involved in the invisibility of women in the Brazilian science scene, public policies created to highlight scientists and the science created by them, in addition to advances made regarding motherhood. The text highlights the different methodological paths traced in the curatorship and expography. The results show the participation of researchers in the process of conception and elaboration of the exhibitions, the exhibition places and their consequences, as well as the quantity of the visiting public and the potential of scientific dissemination for the social inclusion of gender.